The Law on Cooperation for Sustainable Development and Global Solidarity and the international Law: the prevalence of the 2030 Agenda - Díaz Galán, Elena C. (Revista Española de Desarrollo y Cooperación, 2023)
The Spanish Law 1/2023 on Cooperation for Sustainable Development and Global Solidarity represents a step forward in terms of sustainable development and is in line with the 2030 Agenda. The examination of this law raises three questions. On the one hand, the link between its content and the indications of the 2030 Agenda, in relation to the Goals and targets it incorporates. In this regard, the legal nature of the Resolution 70/1 and, above all, the possibility of it acquiring binding force should be examined. In the other hand, the meaning of the principle of solidarity in international law needs to be addressed. And finally, an analysis of the content and scope of this law, in its central aspects must be carried out.